Colored concrete and preparation method thereof

By using raw materials such as white cement, fly ash, iron oxide yellow, acid ore and nano-TiO2 in color concrete, combined with AST-3 anti-flaking agent, the strength and durability of color concrete are solved, and high color saturation and The increase in mechanical strength reduces the impact of ultraviolet rays and water damage.

CN118206342BActive Publication Date: 2024-12-20CHINA RAILWAY CONSTR GRP CHENGDU CONSTR ENG CO LTD +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202410343979.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-25
Publication Date
2024-12-20
Estimated Expiration
2044-03-25

AI Technical Summary

Technical Problem

Existing colored concrete has low mechanical strength and poor color durability, which is susceptible to ultraviolet light and water damage, resulting in color degradation and reduced intensity. Some raw materials such as iron oxide yellow will absorb moisture and reduce the strength of the concrete.

Method used

The raw materials such as white cement, fly ash, iron oxide yellow, acidic ore, anti-flaking agent and nano-TiO2 are used to improve the binding force of raw materials through the hydration reaction of cement, and the dispersion effect of pigments is improved by using AST-3 anti-flaking agent and nano-TiO2. and concrete density, control the particle size and specific surface area of ​​raw materials, and form a good balance effect to enhance color durability and strength.

Benefits of technology

It significantly improves the color saturation and mechanical strength of color concrete, enhances the resistance to high temperature and ultraviolet aging ability, reduces the "whitening" phenomenon, extends the color durability, and meets the market's demand for color concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004757740180000061
    Figure BDA0004757740180000061
  • Figure BDA0004757740180000062
    Figure BDA0004757740180000062
  • Figure BDA0004757740180000071
    Figure BDA0004757740180000071
Patent Text Reader

Abstract

The present invention provides a colored concrete and a preparation method thereof, which belongs to the technical field of special concrete, and is prepared from the following raw materials by mass: 200-400 parts of white cement, 100-200 parts of fly ash, 20-60 parts of yellow iron oxide, 4-8 parts of water reducer, 800-1600 parts of acid ore, 15-35 parts of anti-stripping agent, 15-25 parts of TiO2 and 70-160 parts of water. The present invention enhances the binding force between the raw materials and the pigment through the component action relationship between the raw materials, reduces the internal voids of the colored concrete, improves the mechanical strength and color durability of the colored concrete, reduces the influence of ultraviolet rays, temperature, CO2 and water on the colored concrete, and meets the use demand of colored concrete on the market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of special concrete, and in particular to colored concrete and a preparation method thereof. Background Art

[0002] As a new type of decorative concrete, colored concrete effectively solves the defect of poor aesthetic effect of ordinary concrete and realizes the diversification of concrete colors. Its application in urban construction has a significant effect on improving urban quality and improving the living environment.

[0003] However, colored concrete requires the addition of pigment components, which significantly reduces the strength of colored concrete compared to ordinary concrete. In addition, after service, it will be corroded by corrosive media and its appearance quality will deteriorate, resulting in "whitening" and other problems, which seriously affect the service life of colored concrete. Studies have found that long-term exposure to ultraviolet light and water damage will reduce the adhesion between the mixture and the color powder, and the color powder will be peeled off from the mixture, reducing the color saturation of the colored concrete; CO2 and water will penetrate the voids inside the colored concrete and react with the soluble salts inside the concrete, resulting in "whitening"; in addition, if the voids inside the concrete are reduced, the density will be too high, which will also increase the contact area between the colored concrete and ultraviolet rays, further reducing the adhesion between the mixture and the color powder, causing the color of the colored concrete to change.

[0004] Moreover, some raw materials will also reduce the strength and color durability of colored concrete. For example, yellow concrete usually needs to add yellow iron oxide as a pigment, and yellow iron oxide is needle-shaped. When added to the concrete mixture, it will absorb moisture in the concrete, causing the strength of the hardened concrete to be significantly reduced. In addition, the change in the water-cement ratio will cause the colored concrete to leave many tiny pores, forming tiny pits on the surface of the concrete, scattering the incident light, and thus making the color of the concrete lighter. Therefore, there is an urgent need for a colored concrete with excellent mechanical strength and color durability to meet the current use problems of colored concrete. Summary of the invention

[0005] The purpose of the present invention is to provide a colored concrete and a preparation method thereof, so as to solve the problems of low mechanical strength and poor color durability of the colored concrete in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a colored concrete, which is prepared from raw materials containing the following parts by weight:

[0008] 200-400 parts of white cement, 100-200 parts of fly ash, 20-60 parts of yellow iron oxide, 4-8 parts of water reducer, 800-1600 parts of acidic ore, 15-35 parts of anti-stripping agent, 15-25 parts of TiO2 and 70-160 parts of water.

[0009] Preferably, the particle size of the fly ash is ≤40 μm.

[0010] Preferably, the particle size of the yellow iron oxide is 0.1-0.8 μm.

[0011] Preferably, the water reducer is a polycarboxylic acid high-efficiency water reducer.

[0012] Preferably, the acidic ore is one or more of quartz, phosphate rock and marble;

[0013] The particle size of the acidic ore is 4 to 15 mm.

[0014] Preferably, the anti-stripping agent is AST-3.

[0015] Preferably, the particle size of the TiO2 is 10 to 25 nm.

[0016] The present invention also provides a method for preparing the colored concrete, comprising the following steps:

[0017] The colored concrete is obtained by mixing and curing the raw materials.

[0018] Preferably, the curing temperature is 18-25° C., and the curing time is 28 days.

[0019] The present invention has the following beneficial effects:

[0020] The present invention provides a colored concrete, which is prepared from the following raw materials by mass: 200-400 parts of white cement, 100-200 parts of fly ash, 20-60 parts of yellow iron oxide, 4-8 parts of water reducer, 800-1600 parts of acidic ore, 15-35 parts of anti-stripping agent, 15-25 parts of TiO2 and 70-160 parts of water. The present invention adds white cement, and the binding force between the raw material and the yellow iron oxide is improved through the hydration reaction of the cement itself, which significantly reduces the problem of poor binding force between the raw material and the pigment caused by ultraviolet rays and water, enhances the color durability, and also enhances the strength and high temperature resistance of the colored concrete; AST-3 is used as the anti-stripping agent, and its special end group structure (positively charged amino base neutral group) is used to act with the negative center of the acidic mineral surface, further enhancing the binding force between the raw materials; fly ash is used as the raw material, which has good compatibility with other raw materials, further increases the binding force of the concrete raw materials, and increases the color durability and mechanical strength of the colored concrete.

[0021] The present invention also adds nano-TiO2, which reduces the influence of "whitening" on colored concrete, and controls the particle size of TiO2 to 10-25nm and the particle size of yellow iron oxide to 0.1-0.8μm, so that it has a better dispersion effect in cement, reduces the internal pores of colored concrete, blocks the capillary channels of concrete to make the interior more dense, blocks the reaction between soluble salts in the concrete and CO2, and prolongs the color durability. In addition, nano-TiO2 has a large specific surface area and can absorb more free water, reducing the carrier when the soluble salts in the concrete migrate to the surface, and hindering the formation of "whitening".

[0022] The present invention controls the particle size of fly ash to ≤40 μm, so that the prepared colored concrete has good density. On the premise that the interior is not invaded by CO2 and water, it is also guaranteed not to be eroded by ultraviolet light due to excessive density, thereby enhancing the color durability of the colored concrete.

[0023] The present invention controls the amount of white cement, iron oxide, TiO2 and water to form a good balance effect inside the concrete, thereby preventing the problem of reduced strength and lighter color of the colored concrete due to water absorption by the needle-shaped iron oxide, and ensuring the color saturation of the colored concrete.

[0024] The colored concrete provided by the invention has the advantages of high color saturation, good color durability, high strength and the like.

[0025] The present invention also provides a method for preparing the colored concrete, comprising the following steps: mixing and curing raw materials meeting the mass fraction to obtain the colored concrete. The preparation method provided by the present invention is simple and convenient, reduces production costs, and is suitable for large-scale production. DETAILED DESCRIPTION

[0026] The present invention provides a colored concrete, which is prepared from raw materials containing the following parts by weight:

[0027] 200-400 parts of white cement, 100-200 parts of fly ash, 20-60 parts of yellow iron oxide, 4-8 parts of water reducer, 800-1600 parts of acidic ore, 15-35 parts of anti-stripping agent, 15-25 parts of TiO2 and 70-160 parts of water.

[0028] In the present invention, the mass fraction of white cement is preferably 250 to 350 parts, more preferably 280 to 320 parts, and even more preferably 290 to 310 parts.

[0029] In the present invention, the mass fraction of fly ash is preferably 120 to 180 parts, more preferably 140 to 160 parts, and even more preferably 145 to 155 parts.

[0030] In the present invention, the mass fraction of yellow iron oxide is preferably 25 to 55 parts, more preferably 30 to 50 parts, and even more preferably 35 to 45 parts.

[0031] In the present invention, the mass fraction of the water reducing agent is preferably 4.5 to 7.5 parts, more preferably 5 to 7 parts, and even more preferably 5.5 to 6.5 parts.

[0032] In the present invention, the mass fraction of the acidic ore is preferably 1000 to 1400 parts, more preferably 1100 to 1300 parts, and even more preferably 1150 to 1250 parts.

[0033] In the present invention, the mass fraction of the anti-stripping agent is preferably 20 to 30 parts, more preferably 22 to 28 parts, and even more preferably 24 to 26 parts.

[0034] In the present invention, the mass fraction of TiO2 is preferably 17 to 23 parts, more preferably 18 to 22 parts, and even more preferably 19 to 21 parts.

[0035] In the present invention, the mass fraction of water is preferably 80 to 150 parts, more preferably 90 to 140 parts, and even more preferably 100 to 130 parts.

[0036] In the present invention, the particle size of the fly ash is preferably ≤40 μm, more preferably ≤35 μm, and more preferably ≤30 μm.

[0037] In the present invention, the particle size of the yellow iron oxide is preferably 0.1 to 0.8 μm, more preferably 0.2 to 0.7 μm, and even more preferably 0.3 to 0.6 μm.

[0038] In the present invention, the water reducer is preferably a polycarboxylic acid high-efficiency water reducer.

[0039] In the present invention, the acidic ore is preferably one or more of quartz, phosphate rock and marble.

[0040] In the present invention, the particle size of the acidic ore is preferably 4 to 15 mm, more preferably 6 to 13 mm, and even more preferably 9 to 11 mm.

[0041] In the present invention, the anti-stripping agent is preferably AST-3.

[0042] In the present invention, the particle size of TiO2 is preferably 10 to 25 nm, more preferably 12 to 23 nm, and even more preferably 15 to 20 nm.

[0043] The present invention also provides a method for preparing the colored concrete, comprising the following steps:

[0044] The colored concrete is obtained by mixing and curing the raw materials that meet the conditions.

[0045] In the present invention, the mixing time is preferably 2 to 4 hours, more preferably 2.5 to 3.5 hours, and even more preferably 2.8 to 3.2 hours.

[0046] In the present invention, the curing temperature is preferably 18 to 25° C., more preferably 19 to 24° C., and more preferably 20 to 23° C., and the curing time is preferably 28 days.

[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0048] Example 1

[0049] 200 parts of white cement, 100 parts of fly ash, 20 parts of yellow iron oxide, 4 parts of CC-Al polycarboxylate superplasticizer, 800 parts of quartz, 15 parts of AST-3, 15 parts of TiO2 and 70 parts of water.

[0050] The particle size of fly ash is 40μm, the particle size of yellow iron oxide is 0.1μm, the particle size of quartz is 4mm, and the particle size of TiO2 is 10nm.

[0051] The above raw materials were mixed for 2 hours and then cured at 25°C for 28 days to obtain colored concrete.

[0052] Example 2

[0053] 250 parts of white cement, 120 parts of fly ash, 25 parts of yellow iron oxide, 4.5 parts of CC-Al polycarboxylate superplasticizer, 1000 parts of quartz, 20 parts of AST-3, 17 parts of TiO2 and 80 parts of water.

[0054] The particle size of fly ash is 35μm, the particle size of yellow iron oxide is 0.2μm, the particle size of quartz is 6mm, and the particle size of TiO2 is 12nm.

[0055] The above raw materials were mixed for 2.5 hours and then cured at 18°C ​​for 28 days to obtain colored concrete.

[0056] Example 3

[0057] 280 parts of white cement, 180 parts of fly ash, 55 parts of yellow iron oxide, 7.5 parts of CC-Al polycarboxylate high-efficiency water reducer, 1400 parts of phosphate rock, 30 parts of AST-3, 23 parts of TiO2 and 150 parts of water.

[0058] The particle size of fly ash is 30μm, the particle size of yellow iron oxide is 0.2μm, the particle size of quartz is 13mm, and the particle size of TiO2 is 15nm.

[0059] The above raw materials were mixed for 3 hours and then cured at 20°C for 28 days to obtain colored concrete.

[0060] Example 4

[0061] 310 parts of white cement, 155 parts of fly ash, 45 parts of yellow iron oxide, 6.5 parts of CC-Al polycarboxylate superplasticizer, 1250 parts of marble, 26 parts of AST-3, 21 parts of TiO2 and 130 parts of water.

[0062] The particle size of fly ash is 30μm, the particle size of yellow iron oxide is 0.6μm, the particle size of quartz is 11mm, and the particle size of TiO2 is 20nm.

[0063] The above raw materials were mixed for 3.5 hours and then cured at 23°C for 28 days to obtain colored concrete.

[0064] Example 5

[0065] 400 parts of white cement, 200 parts of fly ash, 60 parts of yellow iron oxide, 8 parts of CC-Al polycarboxylate high-efficiency water reducing agent, 1600 parts of quartz, 35 parts of anti-stripping agent, 25 parts of TiO2 and 160 parts of water.

[0066] The particle size of fly ash is 30μm, the particle size of yellow iron oxide is 0.6μm, the particle size of quartz is 11mm, and the particle size of TiO2 is 20nm.

[0067] The above raw materials were mixed for 3.5 hours and then cured at 23°C for 28 days to obtain colored concrete.

[0068] Performance Testing

[0069] Mechanical properties test

[0070] The colored concrete prepared in Examples 1 to 5 was tested for 7d and 28d compressive strength and flexural strength according to standard GB / T 17671-1999 “Test method for strength of cement mortar”. The results are shown in Table 1.

[0071] Table 1 Mechanical properties test results of colored concrete prepared in Examples 1 to 5

[0072]

[0073] It can be seen from Table 1 that the colored concrete provided by the present application has excellent mechanical strength, solves the problem of low strength of colored concrete, and meets the needs of daily use of colored concrete.

[0074] Calculation formula for total color difference

[0075] Total color difference △E=(△L 2 +△a 2 +△b 2 )1 / 2

[0076] △L=L1-L0 L is the brightness, L1 is the brightness of the colored concrete after being placed in different time and environment, and L0 is the brightness of the colored concrete at the beginning;

[0077] △a=a1-a0 a is the red-green color, a1 is the red-green color of the colored concrete after being placed in different time and environment, a0 is the red-green color of the colored concrete at the beginning;

[0078] △b=b1-b0 b is the blue-green color, b1 is the blue-green color of the colored concrete after being placed in different time and environment, and b0 is the blue-green color of the colored concrete at the beginning.

[0079] UV aging test

[0080] The colored concrete prepared in Examples 1 to 5 was placed in a UV aging box for UV aging experiments, wherein the temperature in the UV aging box was 60° C. and the power of the UV lamp was 60W. The total color difference data after 21 days is shown in Table 2.

[0081] Table 2 UV aging test results of colored concrete prepared in Examples 1 to 5

[0082]

[0083]

[0084] It can be seen from Table 2 that the color of the colored concrete provided in the present application does not change much after long-term ultraviolet irradiation, and has a high resistance to ultraviolet aging.

[0085] Water soaking test

[0086] After the colored concrete prepared in Examples 1 to 5 was immersed in water for 60 days, the total color difference data are shown in Table 3.

[0087] Table 3 Water soaking test results of colored concrete prepared in Examples 1 to 5

[0088] Case Color difference △E Example 1 2.89 Example 2 2.82 Example 3 2.76 Example 4 2.74 Example 5 2.76

[0089] It can be seen from Table 3 that after the colored concrete provided in the present application was immersed for 60 days, no significant fading occurred, and the total color difference did not exceed 3, which showed good resistance to rain erosion.

[0090] Color durability test under CO2 conditions

[0091] The colored concrete prepared in Examples 1 to 5 was placed in a CO2 carbonization box for 56 days, and the color changes are shown in Table 4.

[0092] Table 4 Color durability test results of colored concrete prepared in Examples 1 to 5 under CO2 conditions

[0093] Case Color difference △E Example 1 5.65 Example 2 5.63 Example 3 5.62 Example 4 5.60 Example 5 5.61

[0094] It can be seen from Table 4 that the color of the colored concrete provided by the present invention changes under long-term CO2 conditions, but the overall color difference is small, indicating that it has excellent color durability.

[0095] From the above embodiments, it can be seen that the present invention provides a colored concrete, which is prepared from the following raw materials by mass: 200-400 parts of white cement, 100-200 parts of fly ash, 20-60 parts of yellow iron oxide, 4-8 parts of water reducer, 800-1600 parts of acid ore, 15-35 parts of anti-stripping agent, 15-25 parts of TiO2 and 70-160 parts of water. It can be seen from the test that the colored concrete provided by the present invention has excellent color durability, can be placed in ultraviolet rays, CO2 and rainwater for a long time, has good mechanical strength, and meets the use demand of colored concrete on the market.

[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A colored concrete, characterized in that: Prepared from the following raw materials in parts by weight: 200-400 parts of white cement, 100-200 parts of fly ash, 20-60 parts of yellow iron oxide, 4-8 parts of water reducer, 800-1600 parts of acid ore, 15-35 parts of anti-stripping agent, 15-25 parts of TiO2 and 70-160 parts of water; The particle size of fly ash is ≤40μm; The particle size of the yellow iron oxide is 0.1-0.8 μm; The particle size of the TiO2 is 10-25 nm.

2. The colored concrete according to claim 1, characterized in that: The water reducer is a polycarboxylic acid high efficiency water reducer.

3. The colored concrete according to claim 2, characterized in that: The acidic ore is one or more of quartz, phosphate rock and marble; The particle size of the acidic ore is 4-15 mm.

4. The colored concrete according to claim 3, characterized in that: The anti-stripping agent is AST-3.

5. The method for preparing colored concrete according to any one of claims 1 to 4, characterized in that: It includes the following steps: The colored concrete is obtained by mixing and curing the raw materials.

6. The method for preparing colored concrete according to claim 5, characterized in that: The curing temperature is 18-25° C., and the curing time is 28 days.

Citation Information

Patent Citations

  • Preparation of high brilliant white high weatherability white concrete

    CN101328043A

  • Treatment method for strengthening surface adhesiveness of granite or limestone aggregates

    CN101560072A

  • High-stability colored asphalt concrete and preparation method thereof

    CN111592322A

  • Colored pervious concrete and preparation method thereof

    CN113666696A

  • Colored gravel concrete composition with strong weather resistance and preparation method thereof

    CN114031342A